Understanding lipotoxicity in NAFLD pathogenesis: is CD36 a key driver? - Rada, Patricia; González-Rodríguez, Águeda; García-Monzón, Carmelo; Valverde, Ángela M. (Cell death & disease, 2020)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease worldwide. NAFLD stages range from simple steatosis (NAFL) to non-alcoholic steatohepatitis (NASH) which can progress to cirrhosis and hepatocellular carcinoma. One of the crucial events clearly involved in NAFLD progression is the lipotoxicity resulting from an excessive fatty acid (FFA) influx to hepatocytes. Hepatic lipotoxicity occurs when the capacity of the hepatocyte to manage and export FFAs as triglycerides (TGs) is overwhelmed. This review provides succinct insights into the molecular mechanisms responsible for lipotoxicity in NAFLD, including ER and oxidative stress, autophagy, lipoapotosis and inflammation. In addition, we highlight the role of CD36/FAT fatty acid translocase in NAFLD pathogenesis. Up-to-date, it is well known that CD36 increases FFA uptake and, in the liver, it drives hepatosteatosis onset and might contribute to its progression to NASH. Clinical studies have reinforced the significance of CD36 by showing increased content in the liver of NAFLD patients. Interestingly, circulating levels of a soluble form of CD36 (sCD36) are abnormally elevated in NAFLD patients and positively correlate with the histological grade of hepatic steatosis. In fact, the induction of CD36 translocation to the plasma membrane of the hepatocytes may be a determining factor in the physiopathology of hepatic steatosis in NAFLD patients. Given all these data, targeting the fatty acid translocase CD36 or some of its functional regulators may be a promising therapeutic approach for the prevention and treatment of NAFLD.